El Pensamiento Crítico y Reflexivo desde la Percepción de los Estudiantes de la Licenciatura en Enfermería - Gómez, Gloria Margarita Ruiz; Cisneros, Manuel Antonio López; Terrero, Juan Yovani Telumbre; Rivero, Alma Delia Sánchez; Hernández, Karen Doribel López (European Scientific Journal, ESJ, 2018)
The nursing profession has gone through a process of professionalization in the last decades, which allows to recognize that Nursing emerged as a social activity that has been institutionalized, both in its training and in its work practice, affirming itself as a science, profession, discipline and art. Nursing professionals must generate, promote and apply reflective and critical thinking in their actions, professional, ethical, humanistic and technological (Cardenas, 2015). The objective of this study is to describe the reflexive and critical thinking of the students of the Degree in Nursing of the Faculty of Health Sciences. This is a qualitative study, carried out with 5 students of the faculty of health sciences, we used a representative sample of students who are attending the 2nd, 4th and 8th semester of Nursing Degree. Data were collected through a semi-structured interview (Face to Face). Results: From the constant comparison of data analysis emerged the subcategories 1) critical thinking; 2) reflective thinking; 3) decision making; 4) reflective practice. Conclusions: The results of this study achieved the objective of describing reflective thinking and critical thinking in students of the Nursing Degree in the Faculty of Health Sciences. We identified the empirical categories of the study phenomenon that represents the result attributed to the perception of Critical and Reflective thinking. This resulted in four interrelated sub-categories, reflective thinking, critical thinking, decision-making and reflective practice.